Design of octagonal fractal antenna for ultra wide band communication - Raj .U. R, Resmi; Heera Karunakaran, Prof. (International Journal of Engineering and Technology, 2018)
This paper presents an octagonal fractal antenna for ultra wide band communication. This antenna have small size, lower fabrication cost and multiband characteristics. The antenna is simulated by using HFSS software. It has dimension 32x30mm2.Defected ground plane is used which improves gain. Here.FR4 (Îµr=4.4) having thickness 1.6mm is used as the substrate. The proposed antenna is operating in the frequency range 2.1-12GHz. The resonance frequencies are 2.2GHz, 3.3GHz, 5.6GHz, 9.6GHz and 12GHz.where VSWR â‰¤ 2. It has radiation efficiency of 89.08% and peak gain 10.2dBi .The proposed antenna is applicable in UWB, S, and C and X bands.Â Â